Fintech and central bank digital currency in Australia - David Emery (Asian Development Bank Institute (ADBI), 2019)
This paper sheds light on Australia's fast real-time retail payments system, the New Payments Platform (NPP), which was launched in February 2018 by a consortium of 13 financial institutions, including the Reserve Bank of Australia (RBA). The NPP operates on a 24/7 basis and allows financial institutions to provide immediate funds availability to payment recipients, even where payers and payees have accounts with different financial institutions. This study highlights that there is no strong case for the RBA to issue a retail central bank digital currency given that the safer Next Generation Banknote series is available and the safer NPP, for which the deposits are projected by the Financial Sector Claims Scheme, is installed.
Keywords: G21; G32; F65; F37; 330; central bank digital currency; fintech; Australia